Particle Swarm-Based Micro Air Launch Vehicle Trajectory Optimization Method - Omar, Hanafy; Idres, Moumen; Kafafy, Raed (2012)
The particle swarm-based micro air launch vehicle trajectory optimization method is carried out by formulating a parameter optimization problem, which is solved using a particle swarm optimization procedure. The optimization problem is formulated using a single objective function having the explicit objective to maximize the payload mass. Constraints on terminal conditions are imposed.